Factors contributing to low tuberculosis diagnosis among children aged 0–14 years in Gem Sub County in Siaya County, Kenya - Lilian Atieno Okumu; Daniel Ogungu Onguru; David Otieno Odongo; James Onyuro Oketch (PLoS ONE, 2026)
Tuberculosis (TB) is a top global health challenge, with 1.2 million children aged 0–14 years becoming ill with TB every year. Yet, a significant proportion remain undiagnosed or missed due to diagnostic barriers. This cross-sectional study employing an embedded mixed method approach investigated factors contributing to low tuberculosis diagnosis among children in Gem Sub County, Siaya County Kenya, a high burden region. Data was collected from 71 healthcare workers (HCWs) and 16 respondents across six wards using semi-structured questionnaires and TB register abstraction. Qualitative data underwent deductive thematic analysis while quantitative data was analyzed using descriptive statistics and logistic regression in SPSS version 27. About a third (31.3%) of TB cases in children required three or more facility visits before diagnosis, with some needing up to 12 visits. Costly and inaccessible chest X-rays and GeneXpert underutilization due to difficulties in sputum and alternative sample (gastric lavage, nasopharyngeal aspirates) collection were key diagnostic constraints. Delayed care-seeking due to stigma, misconceptions (56.3% linked childhood TB to HIV) and low TB symptom awareness (37.5% of children presented with ≤2 symptoms) were patient related factors associated with low TB diagnosis. About 56.3% of caregivers sought routine TB screening, but 62.5% sought care only after persistent symptoms. Clinical officers showed substantially higher odds of reporting confidence in sample collection (OR=34, 95% CI 3.81–303.21, p = 0.002) and GeneXpert interpretation (OR=15, 95% CI 3.20–70.39, p < 0.001) than nurses. Trained HCWs were 7.16 times more likely to interpret X-rays accurately (95% CI 2.16–23.67, p < 0.001). Enhanced HCW training, improved diagnostic access, targeted community education on stigma and misconceptions are critical for early TB detection in children.